Evaluation of lithium salts as propellant components - Jančík, Milan; Jalový, Zdeněk; Matyáš, Robert; Zigmund, Jan; Skácel, Radovan; Honcová, Pavla (University of Pardubice, 2019)
Lithium nitrotriazolone dihydrate (LiNTO), lithium ethylenedinitramine hemihydrate (LiEDNA), dilithium ethylenedinitramine dihydrate (Li2EDNA), lithium 5-aminotetrazolate (LiATZ), lithium bis(2,4,6-trinitrophenyl)amine hydrate (LiHexyl), lithium 2,4,6-trinitrophenolate hydrate (LiTNF), and lithium 2,4,6-trinitroresorcinate dihydrate (LiTNR) have been prepared and evaluated with respect to their potential use as a component in the so-called green propellants. Densities and DTA decomposition temperatures were determined. The heat of formation of lithium 5-aminotetratolate was measured using an isoperibolic twin calorimeter. Sensitivities to impact and friction were defined to evaluate handling safety.
Keywords: lithium salts; preparation; sensitivity; DTA; density; heat of formation